2019
DOI: 10.21037/tcr.2019.09.13
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors for breast cancer squamous cell carcinoma and nomogram development for prediction: population-based research

Abstract: Background: To investigate the prognostic survival factors of breast squamous cell carcinoma (BSqCC) and develop a comprehensive nomogram for predicting the survival of breast cancer squamous cell carcinoma. Methods: Data were obtained from the Surveillance, Epidemiology, and End Results (SEER) database to identify patients diagnosed with BSqCC from 1973 to 2015. The data was obtained using SEER Stat 8.3.4 software, collated, and analyzed by Excel 2016 software and SPSS (v25.0). Kaplan-Meier curves were used f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…This type is reported in DMBA-induced cancer rats [11], [37]. This cancer is often malignant and has a bad prognosis [36]. This research also found the existence of necrosis, inflammation, rare tubular image, variation of nucleus shape and size, increased mitosis, and infiltration in the connective tissue around it.…”
Section: Histopathological Type Of Dmba-induced Mammary Cancersupporting
confidence: 52%
See 1 more Smart Citation
“…This type is reported in DMBA-induced cancer rats [11], [37]. This cancer is often malignant and has a bad prognosis [36]. This research also found the existence of necrosis, inflammation, rare tubular image, variation of nucleus shape and size, increased mitosis, and infiltration in the connective tissue around it.…”
Section: Histopathological Type Of Dmba-induced Mammary Cancersupporting
confidence: 52%
“…Adenocarcinoma squamous is also a rare type of human breast cancer [36]. Histopathology showed metaplasia squamous cells and experienced partial or no keratinization.…”
Section: Histopathological Type Of Dmba-induced Mammary Cancermentioning
confidence: 99%
“…In our case, the patient had no other primary site or histological type of breast carcinoma in the affected breast. Treatment is based on mastectomy with axillary lymph node dissection for large tumours, combined with radiotherapy and chemotherapy [8]. Conservative treatment is possible for small tumours [8].…”
Section: Discussionmentioning
confidence: 99%
“…Treatment is based on mastectomy with axillary lymph node dissection for large tumours, combined with radiotherapy and chemotherapy [8]. Conservative treatment is possible for small tumours [8]. Squamous cell carcinoma is not very lymphophilic and in 70% of cases, curage is free of lymph node metastasis [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation